Environmental Protection Laws in India - Pattnaik, Annpurna; Pattnaik, Sibasis (International Journal of Psychosocial Rehabilitation, 2025)
This paper discusses Environmental pollution and the various aspects of it. It talks about how the earth is being continuously contaminated by various activities of humans. The sources of pollution have been discussed, the major source being fossil fuels, the other sources include livestock farming and trading activities. The paper throws light at the various laws that have been brought into force in India to curtail the environmental harm and various decisions given by the Supreme Court by way of Public Interest Litigations. It concludes with the urgent need of the governments of various countries to come together in order to combat the crisis facing the world.